Evaluation of the Infectious Diseases Society of America's Core Antimicrobial Stewardship Curriculum for Infectious Diseases Fellows. (30th June 2021) - Spicer, Jennifer O; Armstrong, Wendy S; Schwartz, Brian S; Abbo, Lilian M; Advani, Sonali D; Barsoumian, Alice E; Beeler, Cole; Bennani, Kenza; Holubar, Marisa; Huang, Misha; Ince, Dilek; Justo, Julie Ann; et al.
Abstract: Background: Antimicrobial stewardship (AS) programs are required by Centers for Medicare and Medicaid Services and should ideally have infectious diseases (ID) physician involvement; however, only 50% of ID fellowship programs have formal AS curricula. The Infectious Diseases Society of America (IDSA) formed a workgroup to develop a core AS curriculum for ID fellows. Here we study its impact. Methods: ID program directors and fellows in 56 fellowship programs were surveyed regarding the content and effectiveness of their AS training before and after implementation of the IDSA curriculum. Fellows' knowledge was assessed using multiple-choice questions. Fellows completing their first year of fellowship were surveyed before curriculum implementation ("pre-curriculum") and compared to first-year fellows who complete the curriculum the following year ("post-curriculum"). Results: Forty-nine (88%) program directors and 105 (67%) fellows completed the pre-curriculum surveys; 35 (64%) program directors and 79 (50%) fellows completed the post-curriculum surveys. Prior to IDSA curriculum implementation, only 51% of programs had a "formal" curriculum. After implementation, satisfaction with AS training increased among program directors (16% to 68%) and fellows (51% to 68%). Fellows' confidence increased in 7/10 AS content areas. Knowledge scores improved from a mean of 4.6 to 5.1 correct answers of 9 questions ( P  = .028). The major hurdle to curriculum implementation was time, both for formal teaching and for e-learning. Conclusions: Effective AS training is a critical component of ID fellowship training. The IDSA Core AS Curriculum can enhance AS training, increase fellow confidence, and improve overall satisfaction of fellows and program directors. Abstract : Evaluation of the IDSA Core Antimicrobial Stewardship Curriculum indicates that infectious diseases fellows and program directors perceived that the curriculum effectively taught foundational stewardship content. The evaluation also suggests that programs implementing the curriculum should prioritize its interactive components. Graphical Abstract: